Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Profesionalitas Guru - Alifatul Fauziyah; Imron Fauzi; Sarwan Sarwan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study examines the managerial competence of school principals in improving the professionalism of teachers at SMPN 9 Jember for the 2023/2024 academic year. The main objective of this study is to identify the steps taken by school principals in the development of teacher professionalism and their impact on the quality of learning. The research method used is qualitative with a case study approach, involving observation, interviews, and analysis of related documents. The results of the study show that the Principal implements his managerial competence through clear planning, teacher involvement in various trainings and seminars. These findings confirm that the strengthening of the managerial competence of school principals contributes significantly to the improvement of teacher professionalism, which in turn has a positive impact on student learning processes and outcomes. This study provides recommendations for the development of more effective managerial strategies in an effort to improve the quality of education in schools.